1997
DOI: 10.1046/j.1365-2141.1997.d01-2000.x
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo neutrophil function in response to three different doses of glycosylated rHuG‐CSF (Lenograstim)

Abstract: Summary. Granulocyte colony-stimulating factor (G-CSF) is being considered as adjuvant treatment for infections in non-neutropenic patients. Normal healthy donors were given rHuG-CSF (Lenograstim) at 2 . 5, 5 . 0 and 7 . 5 g/kg subcutaneously daily for 5 d. Polymorphonuclear leucocyte (PMN) function tests were carried out on peripheral blood PMN before the first injection and at 24 h and 96 h. Circulating PMN levels were also measured at these time intervals and found to be significantly increased with all dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…The high-affinity receptor for Fc␥RI is an early myeloid differentiation marker that is lost at the metamyelocyte stage during normal final maturation of PMN cells and is therefore not expressed on mature cells. It has been demonstrated that G-CSF acts on committed myeloid progenitor cells rather than on mature cells and that G-CSF strongly induces Fc␥RI expression in the precursor cells, resulting in Fc␥RI-positive mature PMN cells (11). Fc␥RI appeared to be the main Fc␥R involved in neutrophil-mediated ADCC assays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high-affinity receptor for Fc␥RI is an early myeloid differentiation marker that is lost at the metamyelocyte stage during normal final maturation of PMN cells and is therefore not expressed on mature cells. It has been demonstrated that G-CSF acts on committed myeloid progenitor cells rather than on mature cells and that G-CSF strongly induces Fc␥RI expression in the precursor cells, resulting in Fc␥RI-positive mature PMN cells (11). Fc␥RI appeared to be the main Fc␥R involved in neutrophil-mediated ADCC assays.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies support that Fc␥R-dependent mechanisms play a role in the effects of rituximab treatment. In vitro studies have confirmed that granulocyte colony-stimulating factor (G-CSF) up-regulates the expression of Fc␥RI (CD64) on polymorphonuclear (PMN) cells, which play an important role in exerting ADCC activities (10,11), and it has been considered that G-CSF augments the effects of rituximab. In addition, experiments using a bispecific antibody (Fc␣RI ϫ CD20) have confirmed that G-CSF enhances cytotoxic activities regulated by Fc␣RI by increasing the number of effector cells, although it does not up-regulate Fc␣RI (CD89) expression (12).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotactic and phagocytic functions were normal or even enhanced, either in in vitro [31] or in vivo [32][33][34] studies. Furthermore, lenograstim should stimulate in vivo infection resistance and act in synergy with antibiotics [32,34,35].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
“…Chemotactic and phagocytic functions were normal or even enhanced, either in in vitro [31] or in vivo [32][33][34] studies. Furthermore, lenograstim should stimulate in vivo infection resistance and act in synergy with antibiotics [32,34,35]. Similar to other haematopoietic growth factors, stimulating properties of lenograstim on human endothelial cells were reported in vitro and in vivo [36][37][38].…”
Section: Pharmacodynamic Propertiesmentioning
confidence: 99%
“…Similar stimulus-dependent responses to rhG-CSF therapy have been reported previously, and several possible mechanisms have been proposed. [19][20][21][22][23][24][25] The rhG-CSF therapy may modulate signal transduction pathways linked to receptors rather than directly altering components of the nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. The enhanced response to fMLP, but not to PMA, a direct activator of protein kinase C, indicates an alteration in signal transduction preceding protein kinase C activation.…”
Section: Discussionmentioning
confidence: 99%